Library Functions Timing Characterization for Source-Level Analysis - Brandolese, C.; Fornaciari, W.; Salice, F.; Sciuto, D. (Design, Automation, and Test in Europe: Proceedings of the conference on Design, Automation and Test in Europe - Volume 1; 03-07 Mar. 2003, 2003)
Execution time estimation of software at source-level is nowadays a crucial phase of the system design flow, especially for portable devices and real-time systems. From a source-level perspective, a call to an external library function is a black-box: only the binary code of such functions is, in fact, available. This paper proposes a methodology for library functions analysis within a source-level estimation framework.